The Relationship between Reason and Revelation in the Practical Commandments of Religion from the Perspective of Ayatollah Javadi Amoli - Hosameddin Sharifi; Hadi Yassaqi (حکمت اسرا, 2025)
Practical rules, in most propositions, are associated with musts and mustn'ts (and are related to what should and should not be). Also, concepts denoting human voluntary actions do not indicate the existence of their external instances. Therefore, the judgments of human volitional actions are considered be hypothetical and Unreal. Accordingly, it seems that these rulings follow the desires and wishes of humans and are devoid of truth and reality. According to Ayatollah Javadi Amoli, these characteristics only apply to practical rulings issued by ordinary people. While practical rulings can have reality and support with real and can have real effects. Then the method of proof and truth-seeking reason and rational demonstrative can be used to understand these actions. In this case, the existence of unreal and hypothetical concepts or unreal and hypothetical instances in these rulings does not prevent their discovery by demonstrative reason and demonstrative mind. On the other hand, the practical rulings of religion are issued based on the trute and reality of human existence and lead to human development and true happiness. Therefore, with the method of demonstrative reason, one can arrive at the same propositions and can reach the same issues that are expressed in religion, and there is correspondence and harmony between the rules of religion and the rules of demonstrative reason in the field of voluntary actions.